On parameter estimation for stochastic logistic growth laws through the maximum likelihood procedure - Rupšys, Petras (Lietuvos matematikos rinkinys, 2004)
A three alternative stochastic logistic growth models (exponential, Verhulst, Gompertz) are used for modelling of growth processes. The aim of this paper is to develop stochastic growth curves for all three stochastic growth models. Estimates of parameters of the stochastic growth models are performed by the maximum likelihood procedure with the local linearization method. The Milshtein discrete time approximation for the solutions of stochastic differential equations is applied.
Keywords: stochastic differential equation; approximation; local linearization; simulation; stand